Analisis pengaruh infrastruktur tingkat upah dan pertumbuhan ekonomi terhadap penanaman modal asing di Provinsi Jambi - Syaparuddin Syaparuddin; Dearmi Artis; Mujli Zamzami (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The objectives of this study are: (1) To analyze how the development of infrastructure, wage rates, economic growth, and foreign investment in Jambi Province in 2000-2017. (2) Analyzing how the influence of infrastructure, wage rates, and economic growth on foreign investment in Jambi Province in 2000-2017. The method used in this research is quantitative descriptive analysis and multiple linear regression with the ordinary least square (OLS) method. F Test results show that simultaneously the infrastructure variables, wage rates, and economic growth have a significant effect on foreign investment in Jambi Province. The t-test shows partially infrastructure and wage levels have a positive and significant effect on foreign investment in Jambi Province. Meanwhile, economic growth has no significant effect on foreign investment in Jambi Province. Keywords: Infrastructure, Wage rate, Economic growth, Foreign investment